Elites, groups, and networks in East-Central and South-East Europe in the long nineteenth century - Pál, Judit 1961-; Popovici, Vlad 1982-; Sorescu-Iudean, Oana 1988- (Central and Eastern Europe, 2022)
Elites should be regarded and approached as gregarious social entities (groups, networks) rather than as outstanding individuals.The volume aims to explore the elites in East-Central and South-Eastern Europe during the long nineteenth century from the perspective of their gregarious tendencies (i.e., groupness), to assess the role of the latter in the elite's decisions and agenda, and to observe the transformations brought in this regard by the changing social and political landscape.While the gregarious tendencies of the members of the elite were rooted in their shared perspectives, in their mutual interests or in the communion of cultural patterns, it is clear that during the process of group formation, kinship ties played an unassailable part, although they were likely never a causal factor.The volume covers the research on elites from the early 18th century to the interwar period, focussing on the Banat, Bessarabia, Bohemia, Bulgaria, Dalmatia, Hungary, Rumania, Serbia, Slovenia, as well as looking into Austria and Austria-Hungary in total